Vision, an Optical User Interface. (July 2019) - Koenderink, Jan
I present a personal account of visual awareness, from a biological, that is, ethological and evolutionary perspective. The facts I select are mainly phenomenological, with a sprinkle of psychophysics, and a snuff of brain theory. This is because I consider visual awareness to be a phenomenological brute fact that has no equivalent in either physiology or cognitive science. My emphasis is on bare fundamentals and integration. I primarily aim at academic understanding.